2017
DOI: 10.1007/s10803-017-3385-9
|View full text |Cite
|
Sign up to set email alerts
|

Written Expression in Individuals with Autism Spectrum Disorder: A Meta-Analysis

Abstract: Although studies exist measuring the effectiveness of writing interventions for students with autism spectrum disorder (ASD), research assessing the writing skills for this group is sparse. The present study identified differences in the written expression of individuals with ASD compared to typically developing (TD) peers, using variables selected from 13 different studies. Using Pearson Product Moment-correlation the relationship between the quality of research studies and the magnitude of the effect sizes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 57 publications
2
37
0
1
Order By: Relevance
“…Research estimates that 60% of children with ASD demonstrate performance in written expression which is significantly discrepant from typically developing peers (Mayes & Calhoun, 2006). These findings are consistent with a meta-analysis of writing achievement in students with ASD which revealed significantly worse performance on (a) handwriting legibility, size, and speed; (b) spelling accuracy; (c) writing complex sentences with details; and (d) length and overall structure of written composition (Finnegan & Accardo, 2018). This is consistent with other research which found significantly lower performance on sentence-level measures such as word count, syntactic complexity (i.e., shorter thought-units),…”
Section: The Importance Of Written Expression Skills For Students Witsupporting
confidence: 76%
See 4 more Smart Citations
“…Research estimates that 60% of children with ASD demonstrate performance in written expression which is significantly discrepant from typically developing peers (Mayes & Calhoun, 2006). These findings are consistent with a meta-analysis of writing achievement in students with ASD which revealed significantly worse performance on (a) handwriting legibility, size, and speed; (b) spelling accuracy; (c) writing complex sentences with details; and (d) length and overall structure of written composition (Finnegan & Accardo, 2018). This is consistent with other research which found significantly lower performance on sentence-level measures such as word count, syntactic complexity (i.e., shorter thought-units),…”
Section: The Importance Of Written Expression Skills For Students Witsupporting
confidence: 76%
“…The mixed findings and limited scope of handwriting interventions included in the current review lend support to Finnegan and Accardo's (2018) suggestion that students with ASD may stand to benefit from intervention methods that have been successfully applied to broader categories of students who struggle with writing. Future research involving students with ASD should consider testing the effects of interventions which successfully included activities in alphabetic knowledge, explicit instruction in handwriting the entire alphabet, and timed practice procedures to build fluency (Graham et al, 2000;Jones & Christensen, 1999).…”
Section: Intervention Components and Outcomesmentioning
confidence: 53%
See 3 more Smart Citations